Efek Bunga Telang (Clitoria ternatea L.) Terhadap Kolesterol Total, LDL, HDL Pada Tikus (Rattus Norvegicus ) - Yustiyani Arifah; Sunarti Sunarti; Rani Prabandari (State University of Gorontalo, 2022)
Dyslipidemia is an abnormality of lipids in the blood, including a decrease in HDL levels and an increase in triglyceride levels, LDL levels and total cholesterol. The high concentration of cholesterol in the blood is one of the causes of atherosclerosis and can further cause hypertension and coronary heart disease. The use of synthetic drugs in the long term can cause unwanted side effects. This study aims to examine the effect of increasing HDL cholesterol levels, decreasing total cholesterol and LDL cholesterol levels from the ethanol extract of Clitoria ternatea L using male rats (Rattus norvegicus). This study used the maceration method of Clitoria ternatea L. then the thick extract obtained was tested for its activity which was divided into 6 treatment groups namely normal control group, positive control, negative control, dose 1 (extract 100 mg/kgBB), dose 1 2 (extract 200 mg/kgBB) and dose 3 (extract 400 mg/kgBB) were then measured for total cholesterol, HDL and LDL. The results showed that the administration of ethanol extract of Clitoria ternatea L was able to reduce total cholesterol levels, LDL and increase HDL levels in male rats. The dose of ethanol extract of Clitoria ternatea L that was most effective in reducing total and LDL cholesterol levels and increasing HDL levels in rats that had been induced by a high-fat diet was dose 3, namely extract 400mg/kgBB.